Developing Interactive Multimedia with Local-Content-Based Narrative Texts for Grade Eight - Pitaloka, Nova Lingga (LINGUA: Jurnal Bahasa dan Sastra, 2014)
Visually literate persons are able to understand, to create and to use images as a means of expression and communication. Understanding the elements, the meanings, and the natures of visual images may lead visually literate persons to be able to use the images for the purpose of teaching English. Integrating the visualimages in the steps of teaching learning process may create better learning atmosphere that trigger the students higher achievement. This paper is aimed to elaborate the nature of visual literacy and the integration of visual literacy component in teaching English.